Key Reasons Behind the Success of Netflix - Miškóciová, Simona; Čajka, Radek, 1983-; Sadílek, Tomáš; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
This thesis investigates the success of Netflix. The goal is to define and describe the most important aspects, as well as steps that have led to the extraordinary growth of this company and to prove that Netflix is in fact a successful company. Researched topics include global expansion, original content creation, customer treatment, business culture, corporate social responsibility, and business viability. The main focus is on explaining and describing the global expansion strategy Netflix used in relation with content production, while applying theory like PESTLE Analysis or Modes of Entry to foreign markets. Moreover, big emphasis is put on investigating the customer satisfaction and preferences by collecting data from real Netflix users. The overall purpose of this thesis is to provide a deeper understanding and insights of Netflix and other Video on Demand providers for someone that might be a user of these streaming services.
Vedoucí práce: Radek Čajka
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses